MITCHELL-BANKS’ VS. FERGUSON AND GROSS HERNIOTOMY IN BOYS OVER TWO: A PROSPECTIVE COMPARISON OF POSTOPERATIVE OUTCOMES - Ahmad, Naveed; Ulas Khan; Tallat Shahzad; Sajjad, Mudassar; Ashraf, Hamza; Imran, Maryum; Iqbal, Aneeq (Journal of Ayub Medical College Abbottabad, 2026)
Background: Inguinal hernia repair in boys traditionally employs Ferguson and Gross Herniotomy (FGH) for older children and Mitchell-Banks’ Herniotomy (MBH) for younger ones, though this age-based distinction is increasingly debated. Objective: To compare postoperative outcomes—primarily scrotal edema—between MBH and FGH in boys over two years of age. Methods: In this prospective cohort study, 136 boys older than two years underwent primary inguinal herniotomy from January 2022 to December 2024 (MBH: 62; FGH: 74). Scrotal edema was assessed clinically on postoperative days 1 and 7. Secondary outcomes included operative time, six-month recurrence, testicular atrophy, and surgical site infection. A p-value <0.05 was considered statistically significant. Results: MBH was associated with a significantly higher incidence of scrotal edema on day 1 (40.3% vs. 5.4%) and day 7 (16.1% vs. 2.7%) (both p<0.05). However, MBH showed shorter operative duration (17.3 ± 3.5 vs. 20.4 ± 4.6 minutes, p<0.001) and lower recurrence rates (1.6% vs. 6.8%, p=0.038). Rates of testicular atrophy and surgical site infection were low and comparable between groups. Conclusion: Despite a higher rate of transient scrotal edema, MBH offers advantages in operative efficiency and recurrence reduction, suggesting it may be a suitable option in older children. Further randomized studies are recommended to confirm these findings.